(untitled) (Damascus University Journal of agriculture sciences, 2024)
This research was conducted at Al-Nashabiya Research Station of the General Commission for Agricultural Research in Damascus Countryside Governorate during the agricultural season (main loop) for the year (2021) in order to study the effect of levels of nitrogen and phosphate fertilizers at the following rates (0%-50%-75%-100%) Of the fertilizer recommendation and in the content of yellow corn Ghouta 82 of nitrogen and phosphorous. The experiment was developed according to a randomized complete block design (RCBD), and the results were analyzed using the statistical program Gen Stat 11. The results of the study showed that the 100% treatment had the highest value in the nitrogen and phosphorous content of leaves, superior to all other treatments, which amounted to (0.4, 1.65%). respectively), and the control treatment (without mineral fertilization) recorded the lowest value. As for the nitrogen content of the grains, the results showed that the nitrogen and phosphorous content of the grains was the highest with significant differences in the treatment 100% (2.05, 0.5%, respectively), while the lowest value was recorded in the control treatment (without mineral fertilization).